Identifying Transformations in Labor and Production Activities of Industrial Park Workers in the Context of the Fourth Industrial Revolution: A Case Study of Dong Nai Industrial Parks - Thi Quynh Anh, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 40 No 4, 2024)
The Fourth Industrial Revolution has been a pivotal force driving transformations in labor and production activities, including innovations in production methods and improvements in working environments. These developments profoundly impact workers across all sectors. In industrial parks, technological advancements significantly influence how workers perform their jobs, necessitating rapid adaptation and continuous skill enhancement in an increasingly professional and competitive working environment. The adoption of technology in production processes enhances efficiency, increases productivity, reduces costs, and improves product quality. However, it also poses challenges such as technological unemployment for workers. Dong Nai, one of the provinces with the largest number of industrial parks in Vietnam, has attracted investors from 43 countries and territories, maintaining its position as an industrial hub in recent years. In Dong Nai’s industrial parks, the intensification of technology transfer and development presents both challenges and opportunities. These dynamics enable workers to enhance their skills, boost competitiveness, and integrate more deeply into global value chains. This paper analyzes key transformations in the labor and production activities of workers in Dong Nai’s industrial parks amidst the context of this new industrial revolution. It also proposes solutions to enhance the capabilities and skills of industrial park workers to meet current demands.